Distinguishing similar volcanic source areas from an integrated provenance analysis: Implications for foreland Andean basins - Varela, Augusto Nicolás (2013)
The Mata Amarilla Formation marks the onset of the foreland stage of the Austral basin, which is composed of mostly nonmarine and littoral siliciclastic sediments, thus providing an opportunity to study the detrital record of the Late Cretaceous southern foreland Andes. Our dataset provides, for the first time, a comprehensive picture of the Late Cretaceous evolution of the Austral foreland basin, constituting a possible analogue to other foreland basins at the foot of the Andes. Sandstones from the Mata Amarilla Formation testify to variable contributions from Jurassic bimodal volcanic rocks of the Deseado Massif and the Patagonian fold-and-thrust belt, in the context of an eastward-advancing orogen. Sandstone petrography shows an overall feldspathic litharenite composition, whereas sandstones coming from the northeast (Deseado Massif) have higher Lv and lower Qp proportions than samples coming from the west (Patagonian fold-and-thrust belt). In the central part of the study area, sandstones are characterized by higher proportions of Qt associated with a greater distance and time of transport relating to its position in the Austral foreland basin. In spite of the increased maturity of sandstone in the central area, X-ray analyses permit recognition of the compositional signature of Mata Amarilla Formation, in which four clay-mineral assemblages were identified: S (rich in smectite), S-K (rich in smectite and kaolinite), Pg (rich in palygorskite), and I/S (rich in illite-smectite mixed layers). S-assemblage evidences well-crystallized smectite, characteristic of volcaniclastic origin. Most smectite was formed during early diagenesis through alteration of labile tuffaceous material derived from the Southern Andes. The stratigraphic variations in clay-mineral assemblages reveal a strong environmental control on their distribution. The transformation of smectite into illite and kaolinite is considered as product of pedogenesis, whereas the presence of palygorskite indicates a coastal environment with paleosol development under poorly drained conditions. Copyright © 2013, SEPM (Society for Sedimentary Geology).